NURSING WORK IN A PEDIATRIC EMERGENCY SERVICE: BETWEEN PLEASURE AND PAIN - Fabricio Alberto Lamb; Carmem Lúcia Colomé Beck; Alexa Pupiara Flores Coelho; Raíssa Ottes Vasconcelos (Universidade Federal do Paraná, 2019)
Objective: Gain knowledge on the experiences of pleasure and pain of nurses who work in a Pediatric Emergency Service.Method: Qualitative exploratory-descriptive study conducted in a university hospital in southern Brazil. Data was collected in April 2015 from nine nursing professionals, through Focus Groups and submitted to thematic content analysis.Results: The experiences of pleasure were associated to liking children, interacting with the children's families, availability of time for providing care, recovery of sick children, teamwork and being recognized for their work by the patients (children) and their families. The experiences of pain were associated to the identification of the nursing worker with the role of mother, to the children's death and suffering, to being the target at which the frustrations of the children's families are directed and to child abuse.Conclusion: The nurses experienced dichotomous feelings of satisfaction and identification with work and frustration due to the daily difficulties and negative outcomes, and role conflicts and emotions are the challenges faced by the workers